Dematiaceous fungal invasion of a bandage contact lens. Issue 2 (18th February 2021) - Dutta, Anirban; Das, Sujata; Behera, Himanshu Sekhara; Mittal, Ruchi
Abstract : A 61-year-old man presented with a 1-month history of reduced vision, redness and pain in the right eye. Examination revealed a bandage contact lens (BCL) in situ with diffuse, pigmented deposits. On removal, the underlying cornea was found to be clear. He had been prescribed the BCL 6 months ago following a deep-seated corneal foreign body removal and was unable to follow-up subsequently. The BCL was sent for microbiological and histopathological evaluation. The culture revealed growth of Cladosporium spp, a dematiaceous fungi. Periodic acid–Schiff staining revealed infiltration of pigmented fungal filaments into the substance of the BCL. While contact lens deposits are a frequent finding, fungal deposits are seldom noted. Irregular follow-up and improper lens maintenance are significant risk factors for the same. Early identification and subsequent removal of the lens is vital to prevent infection of the underlying ocular structures.